Food Security Strategy Based on Local Wisdom in Deli Serdang District - Riska Amalia Lubis; Yusrizal Yusrizal; Rahmi Syahriza; Maryam Batubara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to find out how the main priority strategy for food security based on local wisdom in Deli Serdang is by presenting the internal and external conditions that have been carried out so far., In addition, the researchers also explained several handling urgencies that needed to be implemented so that local wisdom-based food security strategies could be more focused. The method used is a qualitative method using SWOT analysis and QSPM. The number of respondents who filled out the questionnaire was 5 respondents from farmers, the surrounding community, and traditional and religious leaders, and 5 respondents from experts. Based on the results of the SWOT analysis, the strategy quadrants obtained after being processed in the IFE and EFE matrices are in Quadrant I. This indicates that the strategy used is a progressive strategy. This strategy means that food security based on local wisdom in Deli Serdang has strengths and opportunities. Furthermore, in the QSPM analysis, the results show that the main priority strategy that must be carried out is to focus on preserving food security based on local wisdom so that it becomes a business opportunity on an international scale.